Innovative strategies to strengthen teaching-researching skills in chemistry and biology education: a systematic literature review - Alberto, Mera Cabezas Luis; Viviana, Basantes Vaca Carmen; Vladimir, Benavides Enríquez Celso; Fernanda, Parra Alvarez Paulina (Frontiers in Education, 2024)
The dynamic field of scientific education, particularly in chemistry and biology, demands the implementation of innovative teaching strategies, driving the need for continuous research to enhance skills in both educators and students. This systematic literature review (SLR) delves into the evolving landscape of chemistry and biology education research, shedding light on key trends, strategies, and skills. Employing the PRISMA methodology, we scrutinized 81 papers to assess the employment of resources, technologies, and methods conducive to effective learning and research. Searches were conducted in the Scopus and Google Scholar databases, with inclusion criteria spanning English and Spanish studies from the last five years. The analysis reveals a notable shift in recent years, emphasizing the diversification of instructional approaches, integration of sustainable practices, and a heightened focus on fostering essential research skills for both educators and students. The study underscores the significant adaptation to digital tools and virtual environments, potentially influenced by the challenges posed by the COVID-19 pandemic. Remarkable findings include the growing importance of cognitive, social, and emotional competence in student development. This work provides valuable insights for educators, researchers, and policymakers cross-talking the dynamic intersection of teaching and research in chemistry and biology education.